Enzymatic synthesis of enantiomerically pure 1,2-fluorocyclopentanols and 1,2-aminofluorocyclopentanes - Kolodiazhna, O.O.; Veriovka, O.S.; Kolodiazhna, A.O. (Доповіді НАН України, 2019)
Vicinal fluorocyclopentanol are valuable chiral synthetic blocks for the preparation of a number of natural and synthetic biologically active substances Racemic cis-2-fluorocyclopentanols were separated into enantiomers by the kinetically controlled transesterification with vinyl acetate in the presence of lipases in organic media, High enantioselectivity (ee > 98 %) and good yields of compounds were obtained for all substrates using Burkholderia cepacia lipase, The fluorocyclopentanols were converted into enantiomerically pure 1,2-aminofluorocyclopentanes using the Mitsunobu reaction, The enantiomeric purity of the compounds was determined by Mosher's acid derivatization method, and the absolute configurations were determined using the Kazlauskas rule.